Long-Time Stable Colloidal Zn-Ag Quantum Dots With Tunable Midgap-Involved Emission - Sabzevari, Zahra; Sahraei, Reza; Jawhar, Nawzad Nadhim; Yazici, Ahmet Faruk; Mutlugun, Evren; Soheyli, Ehsan (AIP Publishing, 2021)
Quaternary Zn-Ag-In-S (ZAIS) quantum dots (QDs) with efficient, tunable, and stable photoluminescence (PL) emission were prepared via a simple, effective, and low-cost reflux method. The structural analysis revealed the dominance of the quantum confinement effect. The calculated PL emission quantum yield was enhanced from 8.2% to 28.7% with experimental parameters indicating their marked influence on the PL emission properties of the final product. Particularly, it was found that by varying the precursors' feeding ratio, tunable emission from green to red was achieved. A set of direct and indirect pieces of evidence such as the broad-band emission spectrum (FWHM>100nm), large Stokes shift more than 120nm, and predominantly a biexponentially long-lived decay profile with an average lifetime of about 366ns were observed, showing the contribution of midgap localized energy levels in the recombination process. These data were obtained independently on the experimental condition used, which confirmed that this is mostly an intrinsic electronic property of quaternary In-based QDs. Finally, to ensure the stability of QDs in terms of colloidal and optical emission, their emission ability was evaluated after 26 months of storage. Colloidal QDs were still luminescent with strong yellowish-orange color with emission efficiency of similar to 20.3% after 26 months. The combination of synthesis simplicity, compositional non-toxicity, PL emission superiority (strong, tunable, stable, and long lifetime emission), and colloidal stabilities confirms that the present ZAIS QDs are promising candidates for a wide range of applications in biomedicine, anticounterfeiting, and optoelectronics.
Sahraei, Reza/0000-0001-7104-2126; Soheyli, Ehsan/0000-0002-1403-7934; Yazici, Ahmet Faruk/0000-0003-2747-7856; Mutlugun, Evren/0000-0003-3715-5594